Tinjauan Penggunaan Sistem Pendaftaran Online Pasien Rawat Jalan di Rumah Sakit Advent Bandar Lampung Berdasarkan Unsur 5M - Miftahurrohmah Nur Azizah; Supriyanto Supriyanto; Amika Rois (Journal of Educational Innovation and Public Health, 2024)
In this era of globalization, technological progress is growing very rapidly, one of which is in the health sector. The development of various technologies makes it easier in the health sector, one of which is in the registration section. Bandar Lampung Adventist Hospital is one of the hospitals that utilizes technological advances using the Mobile JKN application. To achieve the goal of using the online registration system, 5 elements of management or management facilities are needed, namely: man, money, material, machine, and method. The purpose of this study was to review the use of an outpatient online registration system at the Adventist Hospital in Bandar Lampung. This research was conducted with quantitative descriptive methods, data collection instruments using observations and checklist sheets. From the observation that the man element in the use of the online registration system is not appropriate, this is seen from the HR in charge of the registration section is not a PMIK and of course does not have a medical record STR, the money element in the use of the online registration system is in accordance with this in terms of the budget for the use of an online registration system, the material element is also in accordance with this in terms of several machines used such as the presence of stable WiFi, queue card printing machines, computers, telephones, and televisions that are used as monitors, the machine elements are in accordance with this in terms of their presence an adequate WiFi network in the running system and a registration application system in the form of the Mobile JKN application. And the elements of the method are also in accordance with this in terms of the SOP for online outpatient registration and the registration procedure that is already running.